2020
DOI: 10.1039/c9ob02666e
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective catalytic synthesis of α-aryl-α-SCF32,2-amino acids

Abstract: Novel α-trifluoromethylthiolated-β2,2-amino acids were obtained in high enantiopurities under chiral phase-transfer catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…Based on the widespread interest in asymmetric trifluoromethylthiolation reactions [14,15] and our own recent experience in this field, [12a] we first focused on the asymmetric α‐trifluoromethylthiolation of 3‐cyano p‐methoxybenzyl‐(PMB)‐protected isoindolinone 1 a (Table 1) using different established, as well as newly designed, chiral ammonium salt catalysts A – D (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the widespread interest in asymmetric trifluoromethylthiolation reactions [14,15] and our own recent experience in this field, [12a] we first focused on the asymmetric α‐trifluoromethylthiolation of 3‐cyano p‐methoxybenzyl‐(PMB)‐protected isoindolinone 1 a (Table 1) using different established, as well as newly designed, chiral ammonium salt catalysts A – D (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately however, because of the unexpected pronounced sensitivity that we observed during all these test reactions, and despite the promising selectivities up to e.r . = 91:9, this reaction as such is far from being as robust and practical as other chiral ammonium salt catalyzed reactions that we investigated recently , , …”
Section: Resultsmentioning
confidence: 99%
“…Our group has a strong interest in asymmetric ion pairing catalysis and we recently reported that bifunctional ammonium salt catalysts containing a (thio)‐urea H‐bonding motive (i.e. catalysts A ) can be used for the asymmetric α‐hydroxylation of β‐keto esters 1 by using racemic oxaziridines 2 as the O‐transfer reagents (accompanied by a simultaneous resolution of the oxaziridines 2 as outlined in Scheme B) .…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Waser and co-workers disclosed the synthesis of α-aryl-α-SCF 3 -β 2,2 -amino acids using an enantioselective, ammonium salt-catalysed α-trifluoromethylthiolation of isoxazolidin-5-ones ( Scheme 10 ) [ 44 ]. Starting from compound 30 , the use of catalyst 31 developed by Maruoka [ 45 ] along with CF 3 S-transfer reagent 32 allowed isolation of the quaternary substituted species 33d in excellent yield (90 %) with high enantioselectivity ( e.r .…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%
“…Compound 33d could also be deployed directly in peptide synthesis through initial Boc deprotection followed by α-ketoacid-hydroxylamine (KAHA) ligation, affording dipeptide 36 in 70 % yield.
Scheme 10 Synthesis of α-aryl-α-SCF 3 -β 2,2 -amino acids, Waser and co-workers [ 44 ].
…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%